Goal relevance influences performance monitoring at the level of the FRN and P3 components. (18th April 2016) - Walentowska, Wioleta; Moors, Agnes; Paul, Katharina; Pourtois, Gilles
Abstract: The feedback‐related negativity (FRN) provides a reliable ERP marker of performance monitoring (PM). It is usually larger for negative compared to positive feedback, and for unexpected relative to expected feedback. In two experiments, we assessed whether these effects could be modulated by goal relevance, defined as feedback informativeness (reliability) and/or impact on a person's goals. EEG (64‐channel) was recorded while 30 participants (in each experiment) performed a speeded go/no‐go task across blocks in which the feedback on task performance was deemed either relevant or not. At the ERP level, the FRN component was larger for (frequent) negative compared to (deviant) positive feedback exclusively when the feedback was relevant (Experiment 1). When the probability of positive and negative feedback was balanced (Experiment 2), this valence‐driven FRN effect was absent. However, across these two experiments, the FRN was always larger for irrelevant than relevant feedback. Moreover, the subsequent P300 component was larger for feedback in the relevant than the irrelevant blocks. This effect was valence unspecific in Experiment 1, while in Experiment 2 larger P3 amplitudes were recorded for negative than positive (relevant) feedback. Across the two experiments, a larger correct‐related negativity in the irrelevant than relevant context was also observed, suggesting that PM is flexible. These ERP findings indicate that goal relevance influences feedback (and response) processing during PM, with two nonoverlapping neurophysiological effects: It gates reward prediction error brain mechanisms (FRN effect), before enhancing subsequent motivational processes (P300 effect).